2021
DOI: 10.3390/biomedicines9091129
|View full text |Cite
|
Sign up to set email alerts
|

MARCO+ Macrophage Dynamics in Regenerating Liver after 70% Liver Resection in Mice

Abstract: Background: Macrophages play a key role in liver regeneration. The fates of resident macrophages after 70% resection are poorly investigated. In this work, using the MARCO macrophage marker (abbreviated from macrophage receptor with collagenous structure), we studied the dynamics of mouse liver resident macrophages after 70% resection. Methods: In BALB/c male mice, a model of liver regeneration after 70% resection was reproduced. The dynamics of markers CD68, TIM4, and MARCO were studied immunohistochemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Our own data obtained in a model of 70% liver resection in mice indicate that Tim4 expression in hepatic tissues can rapidly increase in the remnant liver tissue. This increase can be attributed to the influence of boosted endotoxin/LPS blood levels, and this suggestion has been supported by in vitro experiments [ 113 ]. Notably, KCs isolated from the intact liver by magnetic sorting for F4/80 had Tim4 expression levels similar to macrophages differentiated from peripheral blood monocytes isolated by magnetic sorting for CD115 and cultured with M-CSF.…”
Section: The Concept Of Macrophage Niche and Its Application To Kcsmentioning
confidence: 67%
See 3 more Smart Citations
“…Our own data obtained in a model of 70% liver resection in mice indicate that Tim4 expression in hepatic tissues can rapidly increase in the remnant liver tissue. This increase can be attributed to the influence of boosted endotoxin/LPS blood levels, and this suggestion has been supported by in vitro experiments [ 113 ]. Notably, KCs isolated from the intact liver by magnetic sorting for F4/80 had Tim4 expression levels similar to macrophages differentiated from peripheral blood monocytes isolated by magnetic sorting for CD115 and cultured with M-CSF.…”
Section: The Concept Of Macrophage Niche and Its Application To Kcsmentioning
confidence: 67%
“…Considering the reduced Tim4 expression in the ‘newcomers’ [ 61 ], it would be reasonable to expect decreased expression of TIM4 marker in total liver macrophages after resection. However, this proved not to be the case, apparently due to the stimulating effect of LPS on the new, differentiating monocytic macrophages [ 113 ]. It can be concluded that, in this setting, Tim4 expression levels depend more on LPS exposure than on the length of residence in the macrophage niche of KCs [ 113 ].…”
Section: The Concept Of Macrophage Niche and Its Application To Kcsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of the MARCO gene (as well as some other markers) in macrophages originating from liver after a resection procedure was investigated, with a conclusion regarding the increase in MARCO in these cells upon regeneration of liver in a mouse model [ 12 ].…”
mentioning
confidence: 99%